Incidence of facial nerve sacrifice in parotidectomy for primary and metastatic malignancies. (October 2017) - Swendseid, Brian; Li, Shawn; Thuener, Jason; Rezaee, Rod; Lavertu, Pierre; Fowler, Nicole; Zender, Chad
Highlights: 89% of facial nerves were preserved if pain and nerve dysfunction are absent. Full or partial nerve preservation occurred in 60% of all parotidectomies. When sacrifice was required, half only received isolated nerve branch resection. Parotid pain predicted nerve sacrifice, 76.5% compared to 29.3% without pain. Abstract: Introduction: The parotid gland may become involved by primary parotid malignancies and secondarily by metastases from other primary sites. Surgical resection of these tumors can be technically challenging due to the intimate relationship of the parotid gland and the facial nerve. The primary aim of this project was to determine the incidence of facial nerve sacrifice in parotidectomy for primary and secondary malignancies of the parotid. Methods: A retrospective chart review of was performed. Patients who received parotidectomy with final pathology consistent with a malignant neoplasm were included. The primary outcome studied was necessity for facial nerve sacrifice. Co-variates included preoperative facial nerve function, preoperative pain, superficial versus total parotidectomy and pathologic diagnosis. Univariate analysis was performed using student t -test to determine odds ratios. Results: We identified 75 patients who had a parotidectomy for a malignant process in our review. 30 patients had facial nerve sacrifice: 14 total and 16 partial sacrifices. Patients were more likely to require facial nerve sacrifice when they presented with preoperative facial nerve dysfunction [100% vs 19.6%, p = 0.0006, OR 154.3, CI (8.66–2750.9)], pre-op pain [76.5% vs. 29.3%, p = 0.001, OR 7.84, CI (2.23–27.50)], and required excision of both superficial and deep lobes of the parotid gland [64.9% vs 15.8%, p = 0.0001, OR 9.85, CI (3.27–29.66)]. Conclusion: Our data illustrates that many patients with normal facial nerve function, even in the setting of malignancy, can have their facial nerve preserved. Pain, deep lobe involvement and preoperative facial nerve dysfunction are associated with an increased risk of needing at least partial facial nerve sacrifice in the setting of parotid gland malignancies.